From Pen Fini to the Holy Eucharist: Bridging Atoin Meto's Sacred Traditions - Tukan, Antonius Ignasius Nggino; Gonjaga, Januario (International Journal of Indonesian Philosophy & Theology, 2025)
The world has changed so much. The changing of the world has affected all dimensions of human life. It has brought about a change in the role of religious institutions. Moreover, people from different cultures, religions, denominations, and spiritualities come together and share the same land, air, and social life. However, the Good News still has to be spread and shared. Diane M. Millis, the founder of Journey Conversation Project, believes that conversation involves verbal and non-verbal messages. She senses another dimension in human conversation, which is Divine Presence. In this sense, daily encounters can be a means of spiritual conversation. This research will apply qualitative research. The target population of this research is Catholic lay people who are involved in the New Evangelisation movement and pastoral ministry. The findings are as follows: First, creating or capturing a ‘generative theme’. It is important in conversation to reach a generative theme. Second, engaging with people’s lives. This step includes questioning, listening, and responding. Third, sharing Christian faith, the experience of faith. This is a crucial moment in which evangelizers must discern whether or not they will convert the conversation into sharing or providing the interlocutor with knowledge of belief or Christian values. Fourth, giving an authentic affirmation. Fifth, praying. The evangelizers can invite those with whom they have conversations to pray.